Rapid offline isotopic characterisation of hydrocarbon gases generated by micro scale sealed vessel pyrolysis - Ladjavadi, Mojgan; Berwick, Lyndon; Grice, Kliti; Boreham, C.; Horsfield, B. (Pergamon, 2013)
The method of offline coupling of micro scale sealed vessel pyrolysis (MSSV-Py) and gas chromatography-isotopic ratio mass spectrometry (GC-IRMS) was developed using a purpose built gas sampling device. The sampling device allows multiple GC and GC-IRMS injections to quantify the molecular composition and isotopic evolution of hydrocarbon gases (n-C1 to n-C5) generated by artificial maturation of sedimentary organic matter. Individual MSSV tubes were introduced into the gas sampling device, which was then evacuated to remove air and filled with helium at atmospheric pressure. The tube was crushed using a plunger after which the device was heated at 120 °C for 1 min to thermally mobilize and equilibrate the generated gas products. Aliquots of the gas phase were sampled using a gas tight syringe and analysed via GC-FID and GC-IRMS. Hydrocarbon gas yields using this technique have been calculated and compared with those obtained previously by online MSSV pyrolysis of the same samples under the same conditions. The major objective of this study was to investigate the potential isotopic fractionation of generated gaseous hydrocarbons within the gas sampling device as a function of time and temperature. For this purpose several tests using a standard gas mixture have been performed on the GC-IRMS. The analyses showed no isotopic fractionation of C1–5 hydrocarbons within 1 hour, minor δ13C enrichment after 5 hours, and significant enrichment after 22 hours for all the compounds at a temperature of 120 °C.